Ontdekking en bewaring van die Willowmore-versameling van dokumente - 'n gevallestudie - J.C. Loock (Contree)
When a building in the main street of Willowmore was extensively renovated in 1984 a large quantity of documents was acquired by conservation minded individuals. It consists of thousands of letters despatched and received, price lists, market reports, cheques, receipts, waybills, and the books of general dealers. The latter include lists of orders, purchases and of customers as well as what they bought, ostrich feather, wool and mohair registers and some personal documents. All those reflect the socio-economic development of Willowmore and environs between 1863 and 1908.